La composizione architettonica al primo anno. Esperienze di laboratorio tra luogo e memoria. - Abbagnale, Pasquale; Apicella, Davide; Fierro, Maria; Spacagna, Francesca (TeA / Teaching Architecture, 2022)
The volume is the result of reflections of the chair professors of the courses of Architectural and Urban Composition Laboratory, prof. R. Capozzi, Prof. P. Scala, Prof. V. Pezza, Prof. G. Szaniszlò, and the relative didactic experiences carried out in the laboratory courses in the first year of the ARC5UE degree program, a.a. 2020/2021, at the Dept. of Architecture of the University of Naples Federico II (DiARC); it closes with lessons by professors outside the department, who were invited to the cycle of seminars carried out in joint courses. The volume is divided into three parts: Part I - The didactic project between theory and laboratories, Part II - The laboratory experiences, Part III - Architecture, city and archeology. This work has been collated and edited by Arch. Francesca Spacagna, referent of course 1 A; larch. PhD student Maria Fierro, referent of course 1 B; larch. Davide Apicella, coordinator of the 1 C course; larch. Pasquale Abbagnale, referent of course 1 D.